Orientalism and western hegemony in fashion brand's social media advertisements - Syahrul Hidayanto; Moh. Rifaldi Akbar (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
The relentless technology development nowadays has encouraged people worldwide to innovate in things, one of them being advertisements. Although the traditional media is not to be replaced anytime soon, numerous brands are currently establishing social media as a promotional platform by maximizing their social network advertising through various strategies. For example, they use foreign models or celebrities as their brand ambassadors. This strategy, however, ironically brushes off local models and celebrities as potential human resources. Due to this case, this study aims to comprehend fashion brands’ social media advertising strategies by focusing on the background of foreign model preferences. This study uses a qualitative approach and a data-collection technique of in-depth interviews with three owners of professional fashion brands. The results point out that fashion brands prefer foreign models to the local ones as their ambassadors to follow the popular trends, deliver lush visuals, and build a professional, modern, and high-qualified image for the brand and products. Moreover, it is common for Indonesians to disparagingly perceive local brands, as they rather deem local materials and designs below standard. Consequently, this deep-rooted perception successfully perpetuates the socio-cultural hegemony among various practices, including social media advertising and marketing.